The Use of FTIR Spectroscopy in Forensic Practice and Its Potential Future Applications - I. N. Barannikova (Теория и практика судебной экспертизы)
The author examines current applications of infrared spectroscopy in forensic practice and in various areas of science and technology. The paper includes an overview of objects that warrant the use of this forensic analytical technique. It is pointed out that not all capabilities of the method are currently put to use by forensic practitioners. It is also noted that methods based on infrared spectroscopy can be used for quantitative analysis, as well as the study of far and near infrared absorption spectra for forensic purposes.